A Questionnaire-Based Cross Sectional Study on the Prevalence of Substance Abuse among Age 17 to 25 Years in the Chengalpattu Population with Medico Legal Perspectives - Unnamalai R.M.; Dipayan Deb Barman; Vivek Valliappan (Indian Journal of Forensic Medicine and Pathology, 2026)
Background: Substance abuse among young individuals represents a growing public health concern with significant social, psychological, and medico-legal implications. The age group of 17–25 years constitutes a vulnerable transitional phase during which initiation of substance use may result in dependence, health deterioration, academic impairment, and legal consequences.¹ Aim: To determine the prevalence and patterns of substance abuse among individuals aged 17–25 years in the Chengalpattu population and to assess associated medico-legal perspectives. Methodology: A questionnaire-based cross-sectional study was conducted among participants aged 17–25 years residing in Chengalpattu district. Data on socio-demographic characteristics, substance use patterns, reasons for initiation, frequency of use, features suggestive of dependence, and associated behavioral and medico-legal issues were collected using a structured questionnaire. Descriptive and inferential statistical analyses were performed. Results: The overall prevalence of substance use was 9.8%. Alcohol was the most commonly used substance, followed by tobacco and cannabis. A proportion of substance users exhibited features suggestive of dependence. Substance use showed associations with family-related issues, health problems, sleep deprivation, and medico-legal concerns, including exposure to violence. Conclusion: The study demonstrates a notable prevalence of substance abuse among youth in the Chengalpattu population, influenced by socio-demographic and psychosocial factors. The observed medico-legal implications highlight the need for targeted preventive strategies, youth-focused counseling, and coordinated public health and legal interventions to reduce substance-related harm.